(untitled) (Brazilian Geographical Journal, 2013)
Distribution patterns of vegetation around the world are strongly influenced by the climatic factors, and afterwards, the study of vegetacional changes along time should always be in a tight relation with climate. This article will provide an overview of the modern characteristics of Australian and Brazilian humid tropics (rainforests and dry forests ecosystems), as well, along the Last Glacial Maximum (LGM), as focusing on Quaternary environmental upheavals and some trends for Biogeography research. After discussion of papers published during 1991-2008, it was presented research trends related to paleoecology sites and cores analyzed, focusing on three major features: human driven alterations, evolutionary biogeography/conservation and phytoindication and its relation to climate change. It can be concluded that the features of these ecosystems and their range of response to environmental change are applicable to the both characteristics of similar biomes located in the tropical regions of Brazil (South America) and wet tropic Region (Australia).